EVALUATION OF THE INVASIVE POTENTIAL OF L3 JUVENILES OF THE CONTRACAECUM OGMORHINI JOHNSTON & MAWSON, 1941 COMPLEX (NEMATODA; ANISAKIDAE) IN AN EXPERIMENTAL MURINE MODEL - Galeano, Noelia Adelina (2022)
Bibliography indicates that the larvae of the genus Contracaecum are of zoonotic importance. These papers are based on a single clinical case whose conclusions are doubtful and should be confirmed. In the present work, the results of experimental infections in Balb/cAnN mice, with L3 juvenile of the Contracaecum ogmorhini Johnston & Mawson, 1941 complex, are reported. The helminths were obtained in the stripped weakfish, Cynoscion guatucupa (Cuvier, 1830), the second most important commercial fishery resource in Argentina. The parasites were characterized by morphological and molecular criteria. Their population descriptors were established on a sample of 112 hosts. The potential for migration to the skeletal muscle of the fishes was evaluated and the background on experimental infection of Contracaecum spp. in mammalian hosts is discussed. It is concluded that the third-stage juveniles (L3) of the C. ogmorhini complex, can cause injury in humans only if well defined conditions are met, including that the L3 migrate naturally to the host’s musculature (unproven event), that remain viable after gastric digestion by the host and that finds immunological conditions that allow its survival in the digestive tract of the mammal host.